The Effectiveness of Maritime Law Enforcement on Marine Pollution by Commercial Vessels in Indonesia: Institutional Analysis and Implementation of MARPOL 73/78 - Alvon; Indra Sakti; Agus Riyanto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study analyzes the effectiveness of maritime law enforcement against marine pollution by commercial ships in Indonesia by placing the implementation of MARPOL 73/78 and institutional coordination as the main focus. The problems studied depart from the gap between the completeness of legal arrangements, such as UNCLOS 1982, MARPOL 73/78, the Shipping Law, the Law on Environmental Protection and Management, and the Marine Law, and the Maritime Law, and the practices of supervision and enforcement that still face overlapping authority. This study uses a normative juridical method with a statutory approach, a conceptual approach, and a case approach through the analysis of primary legal materials, secondary legal materials, and scientific literature related to pollution from ships. The results of the study show that the effectiveness of law enforcement has not been optimal due to the fragmentation of authority between Bakamla, KKP, TNI AL, Syahbandar/KSOP, KLHK, Polairud, and PPNS; limitations of Port Reception Facilities; weak integration of surveillance data; and inconsistent application of administrative, civil, and criminal sanctions. These findings show that the legal substance is relatively available, but the institutional structure, means of supervision, and compliance culture of shipping business actors are still weak points. Therefore, it is necessary to strengthen integrated coordination mechanisms, standardize follow-up inspection results, improve port waste reception facilities, and apply more consistent sanctions so that marine environmental protection can run more effectively and sustainably.